Attitudes of Teachers of the State of Kuwait towards the effectiveness of using Distance Education in light of some Variables - Alkhaldi, Ahmed Kayyad Hajhouj (Journal of Educational and Psychological Sciences, 2021)
The aim of the research is to identify the trends of male and female teachers of the State of Kuwait towards the effectiveness of using distance education in light of some variables such as gender, specialization, and school stage, through the use of the descriptive and analytical approach, and the creation of a questionnaire consisting of two areas, and its validity and consistency was confirmed, and the research sample consisted of (400) male and female teachers, who were chosen by the stratified random method, and the research reached a set of results, the most important of which are: Attitudes of Kuwaiti teachers towards the effectiveness of using distance education from their point of view, it came with an average degree with an arithmetic mean (3.39), and the results showed the existence of There are statistically significant differences between the responses of the individuals of the research sample due to the variable of gender, and the differences came in favor of teachers in the field of the advantages of using distance education in the educational process, and the tool as a whole, and the absence of differences attributed to the gender variable in the field of disadvantages of using distance education in the educational process, Statistically significant differences between the responses of the individuals of the research sample due to the variable of specialization, and the presence of statistically significant differences between male and female teachers attributed to the stage variable Scientific, and the differences came in favor of male and female teachers who teach in the middle stage, and based on the findings of the research, the researcher recommends holding training courses for male and female teachers in the use of modern programs related to distance education, reducing the teacher’s academic burdens and saving time to apply computer technologies in teaching And setting up motivational, counseling and training programs for teachers, female teachers, and learners in order to accept the use of modern technologies in the educational process.